Diffusion imaging study of the Corpus Callosum in bipolar disorder. (30th January 2018) - Prunas, Cecilia; Delvecchio, Giuseppe; Perlini, Cinzia; Barillari, Marco; Ruggeri, Mirella; Altamura, A. Carlo; Bellani, Marcella; Brambilla, Paolo
Abstract: Structural and diffusion imaging studies have provided some evidence of abnormal organization of Corpus Callosum (CC) in Bipolar Disorder (BD). Therefore, by using Diffusion Weighted Imaging (DWI), which allows to build subtle prediction models of fiber integrity for white matter (WM) tracts, this study aims to further explore the microstructure integrity of CC in BD patients compared to matched healthy controls. Twenty-four chronic patients with BD and 35 healthy controls were included in the study. Circular regions of interest were placed, on diffusion images, in the left and right side of callosal regions (i.e. rostrum/genu, anterior body, posterior body, splenium) and the Apparent Diffusion Coefficient (ADC) was then calculated. Significantly increased ADC values were found in right anterior body and in right splenium in BD patients compared to healthy controls (all p < 0.05, Bonferroni corrected). In this study, we found abnormally increased ADC callosal values in BD suggesting microstructural anomalies specifically in the right hemisphere. Interestingly, this finding further supports the presence of an altered inter-hemispheric communication between frontal and temporo-parietal association areas in patients with BD, which may ultimately result in clinical symptoms and cognitive deficits. Highlights: Diffusion weighted Imaging investigation of the Corpus Callosum in bipolar disorder. Abnormally higher ADC values in right anterior body and splenium in BD patients. Importance of studying callosal integrity and dysmyelination processes in BD.